2004
DOI: 10.1253/circj.68.473
|View full text |Cite
|
Sign up to set email alerts
|

Sinus Node Function in Patients With Brugada-Type ECG

Abstract: n 1992 Brugada et al reported 8 patients with right bundle branch block and persistent ST segment elevation in the right precordial leads. 1 These patients experienced episodes of syncope, and polymorphic ventricular tachycardia or VF was induced by programmed electrical stimulation (PES). It has been reported that 10-20% of cases of Brugada syndrome are caused by cardiac sodium channel mutation, 2-4 and impaired sodium channel function can explain the characteristic ST segment morphology and the occurrence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 32 publications
(38 reference statements)
1
34
0
Order By: Relevance
“…In 10 of these 11 patients, ventricular fibrillation was also induced by 2 or 3 right ventricular extrastimuli. 17 In 1 patient, Wolff-Parkinson-White (WPW) syndrome and atrioventricular nodal re-entrant tachycardia (AVNRT) were first diagnosed, and BS was diagnosed after accessory pathway ablation. BS was accompanied by AVNRT in another patient.…”
Section: Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 10 of these 11 patients, ventricular fibrillation was also induced by 2 or 3 right ventricular extrastimuli. 17 In 1 patient, Wolff-Parkinson-White (WPW) syndrome and atrioventricular nodal re-entrant tachycardia (AVNRT) were first diagnosed, and BS was diagnosed after accessory pathway ablation. BS was accompanied by AVNRT in another patient.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…There is evidence that some patients with BS exhibit paroxysmal atrial fibrillation (AF) and/or sick sinus syndrome. [12][13][14][15][16][17] However, only a few studies have reported on the mechanisms that explain the association of BS with AF. 12,18 Thus, in this study, we evaluated the electrical abnormalities of the atrial myocardium based on the filtered P-wave duration (FPD) using the P-wave triggered signalaveraged ECG and on atrial vulnerability tested by atrial premature stimulation.…”
mentioning
confidence: 99%
“…9,10 There are several clinical reports of BS with sinus node dysfunction. [9][10][11][30][31][32][33] Genetic analysis could be examined in only 1 of the 4 patients with SSS and Brugada-type ECG, which was negative in our study population.…”
Section: Hayashi H Et Almentioning
confidence: 85%
“…VF is more easily induced by the programmed electrical stimulation from the RV outflow tract than that from the RV apex. Prolonged sinus node recovery time and sino-atrial conduction time as well as slowed atrial conduction and atrial standstill have been reported in association with the syndrome (40).…”
Section: Unmasking Of Brugada Phenotype By Other Agents and Conditionsmentioning
confidence: 99%